Operative posterior disconnection in epilepsy surgery: Experience with 29 patients. (29th August 2019) - Kalbhenn, Thilo; Cloppenborg, Thomas; Wörmann, Friedrich G.; Blümcke, Ingmar; Coras, Roland; May, Theodor W.; Polster, Tilman; Simon, Matthias; Bien, Christian G.
Abstract: Objective: It has been suggested that multilobar epilepsies caused by lesions restricted to the posterior cerebral quadrant (ie, the parietal, temporal, and occipital lobes) can be treated successfully by a procedure termed posterior disconnection. The objective of the present paper was to identify determinants of the epileptological outcome following posterior disconnection surgery. Methods: The authors retrospectively analyzed a series of 29 consecutive patients undergoing posterior disconnection surgery between 2005 and 2017 for the treatment of refractory posterior quadrantic epilepsy. Specifically, all presurgical and postoperative magnetic resonance (MR) studies were reviewed to identify cases with an incomplete disconnection, or the presence of a more widespread pathology involving the whole hemisphere rather than only its posterior quadrant. In addition, we reevaluated all presurgical video–electroencephalography (EEG) reports. Results: Seizure‐free (International League Against Epilepsy [ILAE] 1) after surgery were 3/3 patients with EEG findings restricted to the posterior quadrant, 0/7 patients who had propagation of epileptic activity to the contralateral frontal lobe, and 11/19 (57.9%) who showed propagation to ipsilateral frontal and/or contralateral posterior. Eleven of 13 (84.6%) patients with purely posterior quadrantic magnetic resonance imaging (MRI) findings (as retrospectively diagnosed by neuroimaging) vs 3/16 (18.8%) cases with additional subtle abnormalities outside the posterior quadrant became seizure‐free ( P = .001). Eleven of 16 (68.8%) patients with complete disconnections were seizure‐free vs only 3/13 (23.0%) cases with leftover temporal lobe tissue with contact to the insula ( P = .025, both Fisher's exact test). Significance: A posterior disconnection is a technically demanding but very effective operation for posterior quadrantic epilepsy. Good epileptologic outcomes require not only that the epileptogenic lesion does not extend beyond the confines of the disconnected cerebral volume but also the absence of subtle MRI abnormalities, more widespread than the clear‐cut lesion of the posterior quadrant. Hemispheric or contralateral (particularly frontal) propagation of the epileptic activity may also indicate the presence of a hemispheric rather than posterior quadrantic pathology.